Budaya Politik pada Generasi Millenial - Fajar Nugraha (Jurnal Inovasi Komunikasi, 2025)
Abstract. PKS muda as a party wing based on millennial generation, be interesting for researchers to examine the political culture of young PKS members, especially on social media Twitter and Facebook. This study aims to determine the political ideas, political language and values of political culture about the 2019 general election on social media twitter and facebook on young PKS members, as well as knowing the patterns of political interaction about the 2019 general election that occurred on twitter social media on Young PKS members. The study uses qualitative methods, a virtual ethnographic approach with the theory of social-cyber reality, with the research subject of young PKS members, and the object of political culture research of young PKS members on Twitter and Facebook social media. The results showed the political culture of young PKS members contained in political ideas are the idea of flattering and defending supported parties / candidates, invitation to vote and criticize political opponents and election organizers. The political culture contained in political language uses more forms of description, narration and persuasion discourse. The political culture associated with pattern of political interaction is much influenced by the reality of online and offline spaces which aim to lead public opinion through shar or retweet, replays or comments, and hashtags. Emerging political cultural values include values of courage, care, optimism, enthusiasm, trust in leaders and trust in elections as part of political jihad.